El acento proto-vasco - Martínez, Mikel (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2004)
In this article, a thorough criticism of the main issues concerning the Basque accentuation is performed. In point 1, a synchronic description of the different Basque accentual types as described in Michelena (1972) and Hualde (1997) is carried out. Type I corresponds to western varieties (specially V and G.) and is characterized by the presence of certain accentually marked roots and morphemes, like the plural suffix. Type II corresponds to the Northeastern corner of the Basque-speaking territory (Suletin. and Roncalese dialects) and its main feature is that the stress (witch is clearly intensive) falls nearly regularly on the penultimate syllable in the bulk of the lexikon. Type III corresponds roughly to High Navarrese (AN) and is a derivation of Type II by means of a tendency towards the «columnization» of the accent throughtout the paradigm. Type IV is still operative in the low part ofthe Bidasoa valley and according to it most word are stressed on the second syllable from the beginning. Point 2 is an explanation of the different attempts to reconstruct the common accent. In particular, we discuss the proposals made by Martinet (1950, 1955) (accent on the first syllable), Michelena (1958) (accent on the second syllable) and Hualde (1993) (phrase-final accent with no word-level prominence). In point 3, we discuss all the elements that are relevant in the diachronic analysis. Thus, we argue that Lakarra's (1995) theory of the root provides support for the accent-on-second theory, since some etymologies proposed by him seem to suggest that in some bisyllabic roots the first element has lost some phonic substance, whereas the second remains untouched which may imply pretonic position of the former (*han-ker "wicked animal" > aker "billy goat"). Finally, in point 4 we sketch out how the chronological development from that commmon accent system to the historical types may have taken place.